Safety and Immunogenicity of Improved Shigella O-Specific Polysaccharide-Protein Conjugate Vaccines in Adults in Israel - Passwell, Justen H. (American Society for Microbiology, 2001)
Data suggest that the O-specific polysaccharide (O-SP) domain of the lipopolysaccharide (LPS) of Shigella species is both an essential virulence factor and a protective antigen and that a critical level of serum immunoglobulin G (IgG) to this antigen will confer immunity to shigellosis. Because covalent attachment of polysaccharides to proteins increases their immunogenicity, especially in infants and in young children, the O-SP of Shigella species were bound to medically useful proteins, and the safety and immunogenicity of the resultant conjugates were confirmed in adults and 4- to 7-year-old children. Succinylation of the carrier protein improved the immunogenicity of Shigella conjugates in mice and increased their yield. Based on these results, a clinical trial of O-SP conjugates of Shigella sonnei and Shigella flexneri 2a bound to succinylated mutant Pseudomonas aeruginosa exotoxin A (rEPA(succ)) or native or succinylated Corynebacterium diphtheriae toxin mutant (CRM9 or CRM9(succ)) was conducted in healthy adults. The conjugates were safe and immunogenic. S. sonnei-CRM9, S. sonnei-CRM9(succ), and S. sonnei-rEPA(succ) elicited significant rises of geometric mean (GM) IgG anti-LPS within 1 week of injection (P < 0.001). At 26 weeks, the GM anti-LPS levels elicited by these three conjugates were similar and higher than their prevaccination levels (P < 0.0001). GM IgG anti-LPS levels elicited by S. flexneri 2a-rEPA(succ) were significantly higher than those elicited by S. flexneri 2a-rCRM9(succ) at all intervals after injection. At 26 weeks, the levels of IgG anti-LPS in vaccinees were higher than their prevaccination levels (P < 0.0001). The serum antibody responses were specific, as there was no significant rise of anti-LPS to the heterologous O-SP in any vaccinee. Both conjugates elicited statistically significant rises of serum antibodies to the injected carrier protein. At 6 months, these five Shigella conjugates elicited higher fold rises than similar conjugates (D. N. Taylor et al., Infect. Immun. 61:3678–3687, 1993). Based on these data, we chose S. sonnei-CRM9 and S. flexneri 2a-rEPA(succ) for evaluation in children.